Graded hypoxia and blood oxidative stress during exercise recovery. Issue 1 (2nd January 2016) - Peters, Bridget; Ballmann, Christopher; Mcginnis, Graham; Epstein, Erin; Hyatt, Hayden; Slivka, Dustin; Cuddy, John; Hailes, William; Dumke, Charles; Ruby, Brent; Quindry, John
Abstract: Altitude exposure and exercise elicit oxidative stress in blood; however, exercise recovery at 5000 m attenuates oxidative stress. The purpose was to determine the altitude threshold at which blood oxidative stress is blunted during exercise recovery. Twelve males 18–28 years performed four-cycle ergometry bouts (60 min, 70% VO2 max, at 975 m). In a randomised counterbalanced crossover design, participants recovered 6 h at 0, 1667, 3333 and 5000 m in a normobaric hypoxia chamber (recovery altitudes were simulated by using a computerised system in an environmental chamber by lowering the partial pressure of oxygen to match that of the respective altitude). Oxygen saturation was monitored throughout exercise recovery. Blood samples obtained pre-, post-, 1 h post- and 5 h post-exercise were assayed for ferric-reducing antioxidant plasma, Trolox equivalent antioxidant capacity, uric acid, lipid hydroperoxides and protein carbonyls. Muscle biopsies obtained pre and 6 h were analysed by real-time polymerase chain reaction to quantify expression of hemeoxgenase 1, superoxide dismutase 2 and nuclear factor (euthyroid-derived 2)-like factor. Pulse oximetry data were similar during exercise, but decreased for the three highest recovery elevations (0 m = 0%, 1667 m = −3%; 3333 m = −7%; 5000 m = −17%). A time-dependent oxidative stress occurred following exercise for all variables, but the two highest recovery altitudes partially attenuated the lipid hydroperoxide response (0 m = +135%, 1667 m = +251%, 3333 m = +99%; 5000 m = +108%). Data may indicate an altitude threshold between 1667 and 3333 m, above which the oxidative stress response is blunted during exercise recovery.